Improving the Accounting of Investment Activity of Enterprise - Аtamas Oleksandr Р.; Klimova Nataliya А. (Bìznes Inform, 2023)
The aim of the article is to study the current state of carrying out the investment and its impact on the formation of data on the investment activity of enterprise in the accounting system. In accordance with the set goal, the study solved the following tasks: systematize, closer define and supplement the theoretical foundations of investment policy at enterprises; identify current problems of investment policy at enterprises; propose scientific and practical ways to improve the accounting of investment activity of enterprise. During the analysis, systematization and generalization of scientific works of numerous scholars, the need for a comprehensive study of this issue was determined. As a result of the study, a scheme of dependence of the level of risk on the type of investment has been composed, the factors influencing the level of development of the investment policy of enterprise have been considered, the constituent elements of the accounting policy of investment activity of enterprise have been analyzed. Prospects for further research in this direction are to improve the accounting of investment activities of enterprises in any sector of the national economy, given that a new stage of Ukraine’s integration into the European and world communities has begun. Ensuring Ukraine’s integration into the modern global economic system as a technologically developed country with an appropriate level of development of investment policy in the industrial sector and an ensured accounting of investment activities should become a top national priority.